AUTHENTIC ASSESSMENT IN ELT: HOPES, CHALLENGES, AND PRACTICES - Tono Suwartono; Cici Riyani (Universitas Muria Kudus, 2019)
The aim of this paper is to provide an overview of the need of authentic assessment in English language teaching in Indonesia. After the implementation of 2013 curriculum (Discovery Learning Curriculum), the evaluation that must be done by teacher is not only emphasized on cognitive domain but also in psychomotoric and affective domains. The authors reviewed the authentic assessment from both the information literacy and instructional design which can be applied by EFL teachers in their classes. Overall, this paper gives an outlook on what, why and how all about authentic assessment in ELT.